English orthographic depth among Malay learners at a primary school - Khairunnadiah Mohd Samuddin,; Pramela Krish, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study concerns the spelling difficulties in English as a second language among young Malay learners. The objectives of this study are to identify and categorise the spelling errors produced by these learners and to investigate the linguistic factors for the error productions. This study employs Wardhaugh’s Contrastive Analysis as the main approach and Orthographic Depth Hypothesis as the foundation of the research. The Contrastive Analysis approach indicates that the linguistic differences between L1 and L2 may cause difficulties in L2 learning. The theoretical basis of this study claims that the degree to which an orthography deviates from easy one-to-one letter-sound plays a major role in L2 learner’s spelling performance. This study adapts a spelling assessment from El-Dakhs and Mitchell that tests students’ phonological, orthographic and morphological awareness and knowledge. The sample of this study consists of 46 eleven-year-old Malay students from a selected school in Selangor. The data for the study was gathered from the subjects’ responses in the assessment and interviews with selected students based on their test scores. The findings showed that the learners’ spelling performance was poorer in the orthographic tasks and better in the morphological and phonological tasks, suggesting the salience of orthography in the early stage of L2 learning. Based on the results of this study, it is recommended that educators employ orthographic, phonic-based and form-meaning approaches in their teaching to enhance their students’ spelling proficiency so as to assist their students in their literacy development.